Origin of electronic absorption spectra of MLCT-excited and one-electron reduced 2,2′-bipyridine and 1,10-phenanthroline complexes - Záliš, Stanislav; Consani, Cristina; Nahhas, Amal El; Cannizzo, Andrea; Chergui, Majed; Hartl, František; Vlček, Antonín (Inorganica Chimica Acta, 2011)
Electronic absorption spectra of one-electron reduced and MLCT excited states of metal α-diimine complexes in the UV region are similar in appearance and a predominantly IL origin, whereas the visible absorption bands are of a different nature, mostly IL and LMCT, respectively. [Display omitted] ► Reduced and excited-state UV absorption spectra of diimine complexes are similar. ► Spectral similarities in the visible spectral region are largely coincidental. ► UV transitions of reduced and excited states have at least 50% IL character. ► Visible transitions are predominantly IL and LMCT for reduced and excited states, resp. ► Overlap of reduced- and excited-state spectra complicates electron transfer studies. UV–Vis absorption spectra of one-electron reduction products and 3MLCT excited states of [ReICl(CO)3(N,N)] (N,N=2,2′-bipyridine, bpy; 1,10-phenanthroline, phen) have been measured by low-temperature spectroelectrochemistry and UV–Vis transient absorption spectroscopy, respectively, and assigned by open-shell TD-DFT calculations. The characters of the electronic transitions are visualized and analyzed using electron density redistribution maps. It follows that reduced and excited states can be approximately formulated as [ReICl(CO)3(N,N−)]− and ∗[ReIICl(CO)3(N,N−)], respectively. UV–Vis spectra of the reduced complexes are dominated by IL transitions, plus weaker MLCT contributions. Excited-state spectra show an intense band in the UV region of ∼50% IL origin mixed with LMCT (bpy, 373nm) or MLCT (phen, 307nm) excitations. Because of the significant IL contribution, this spectral feature is akin to the principal IL band of the anions. In contrast, the excited-state visible spectral pattern arises from predominantly LMCT transitions, any resemblance with the reduced-state visible spectra being coincidental. The Re complexes studied herein are representatives of a broad class of metal α-diimines, for which similar spectroscopic behavior can be expected.